Antioxidant activity of grape skin aqueous extracts from pressurized hot water extraction combined with electron paramagnetic resonance spectroscopy - Sťavíková, Lenka; Polovka, Martin; Hohnová, Barbora; Karásek, Pavel; Roth, Michal (Talanta, 2011)
Pressurized hot water extraction (PHWE) was employed to prepare extracts from dried grape skin of two wine grape varieties (St. Laurent and Alibernet) at various temperatures (from 40 up to 120°C) and amounts of sample (0.5, 1.0 and 1.5 g). To assess the antioxidant activity of the extracts, electron paramagnetic resonance (EPR) spectroscopy was applied involving DPPH and ABTS(+) assays. Other extract characteristics including HPLC profile of anthocyanins and total phenolic compound content were obtained as well. PHWE has also been compared with earlier results of extractions of the same grape skin samples with compressed methanol and compressed ethanol under the conditions of pressurized fluid extraction (PFE). From this comparison, PHWE emerges as the more benign and efficient extraction method to recover valuable phenolic antioxidants from grape skins for the prospective use in functional food supplements.
Keywords: Antioxidants; Plant Epidermis; chemická frakcionace; vysoká teplota; rostlinné extrakty; Hot Temperature; vysokoúčinná kapalinová chromatografie; tlak; spektrofotometrie ultrafialová; Electron Spin Resonance Spectroscopy; voda; Chromatography, High Pressure Liquid; Water; Spectrophotometry, Ultraviolet; antioxidancia; Plant Extracts; epidermis rostlin; elektronová paramagnetická rezonance; Vitis; Chemical Fractionation; Pressure